Health- related quality of life in diabetic people with different vascular risk - Oliva Juan; Fernández-Bolaños Antonio; Hidalgo Álvaro (BMC, 2012)
Abstract Background The number of papers on the health related quality of life of patients with DM has grown in recent years but fewer studies have drawn comparisons between diabetic persons and the general population considering different risk groups. The aim of this study is to examine health related quality of life (HRQOL) in people with diabetes mellitus (DM) and to analyze the differences in HRQOL adjusting by vascular risk. Methods The data used in this analysis was obtained from the responses of 15,926 individuals who participated in the 2006 Catalonia Health Survey. Our analysis provides a number of multivariate statistical models designed for studying HRQOL, based on the EQ-5D questionnaire, controlling for demographic factors of survey participants and variables that identify diagnosed illnesses and health problems. Results Our findings suggest there is a significant, moderate negative relationship between DM and HRQOL in comparison with non diabetic people (absolute value of the coefficient ranges between −0.04 and −0.054 points on a scale of 1). A further analysis of subgroups reveals that diabetics who have not had vascular risk factors neither vascular diseases do not have a diminished HRQOL when compared to the non-diabetic population in general, when other factors are controlled for. In contrast, a comparison of diabetics and non-diabetics who exhibit vascular disease or risk factors for vascular disease reveals HRQOL is significantly diminished to a greater extent for those with diabetes (between 0.152 and 0.175 points loss when comparing a non-diabetic person with a diabetic with vascular disease). Also, HRQOL in diabetic patients who have additional risk factors or a vascular disease are lower than people non-diabetic who have additional risk factors or a vascular disease. When we focus our analysis to the EQ-5D dimensions, we observe that diabetic persons who are neither at risk for nor have a diagnosed vascular disease are no more likely than non-diabetics to report problems. However, diabetic patients who have additional risk factors for vascular disease or a diagnosed vascular disease are significantly more likely to report moderated or severe problems in 4 of the 5 dimensions of EQ-5D. Conclusions The HRQOL of a person who has diabetes is not necessarily lower than for a non-diabetic. Control of risk factors associated to vascular diseases is a key factor for an enhanced quality of life. Vascular disease or risk factors for vascular disease, on the other hand, are associated with a significantly diminished quality of life for diabetic persons.